2018
DOI: 10.1177/0308022617752110
|View full text |Cite
|
Sign up to set email alerts
|

An occupational perspective in hand therapy: A scoping review

Abstract: Introduction: There have been calls for the occupational therapy profession to realign with its values around occupation. However, the profession faces challenges in practice areas that have historically been underpinned by a biomechanical approach, such as hand therapy. The aim of this scoping review was to describe what is known about an occupational perspective in the hand therapy literature. Method: This scoping review utilised a recognised five-step approach. A search was conducted in four databases for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Indeed, in 2011, Robinson et al [ 67 ] warned the scientific community that the influence of the biomedical model of health on OT limited the integration of occupation-based practice for people with CP, the latter being the central value of OT. More recently, Burley et al [ 84 ] also witnessed two competing perspectives, biomechanical and occupational, that are present in OT services in the hand therapy literature. They noticed that whilst there has been some integration of an occupational perspective, a bottom-up approach, an inconsistent use of terminology to describe what could be framed as occupations, and a lack of an occupation-based performance perspective persist throughout the OT clinical process.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in 2011, Robinson et al [ 67 ] warned the scientific community that the influence of the biomedical model of health on OT limited the integration of occupation-based practice for people with CP, the latter being the central value of OT. More recently, Burley et al [ 84 ] also witnessed two competing perspectives, biomechanical and occupational, that are present in OT services in the hand therapy literature. They noticed that whilst there has been some integration of an occupational perspective, a bottom-up approach, an inconsistent use of terminology to describe what could be framed as occupations, and a lack of an occupation-based performance perspective persist throughout the OT clinical process.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review (Burley, Di Tommaso, Cox & Molineux, 2018) revealed that patients with hand injuries experienced occupational issues and found rehabilitation informed by an occupational perspective to be motivating (Bamford & Walker, 2010;Cheung, Clemson, O'Loughlin & Shuttleworth, 2016;Engstrand, Krevers & Kvist, 2015). Other themes from the scoping review included: the assumption that a bottom-up, biomechanical approach would improve occupational performance; a high focus placed on occupational outcome measures; and the use of informal discussion as an occupational strategy (Powell & Von Der Heyde, 2014;Weinstock-Zlotnick & Bear-Lehman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which patients are affected in their activities of daily living (ADL) following a disorder differs, but as we use our hands in almost all ADL, a hand-related disorder often causes impaired functioning even after years. [2][3][4] Although illness perception has gradually changed over recent decades from a narrow biomedical approach to a broader and more dynamic perception, the biomedical approach remains dominant for most health professionals. 5 This also applies to hand therapy where successful treatment is often judged by improvements of range of motion (ROM) and handgrip strength rather than achieving client-centered and occupation-focused goals.…”
Section: Introductionmentioning
confidence: 99%
“…5 This also applies to hand therapy where successful treatment is often judged by improvements of range of motion (ROM) and handgrip strength rather than achieving client-centered and occupation-focused goals. 4,6,7 Studies exploring patients' recovery found that patients valued occupational performance as a more important outcome than improvements in objective measures, e.g. ROM and handgrip strength, 4 and further, that a focus on occupation improved client motivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation